Precise morphological mapping of high plex neurodegenerative and neuroinflammation protein targets in human and mouse FFPE brain tissue with the GeoMx™ digital spatial profiler: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Rosenbloom, Alyssa; Bahrami, Arya; Kuhar, Jamie; Miller, Kelly; Liang, Yan; Geiss, Gary; Beechem, Joseph M.
Abstract: Background: Neurodegenerative diseases, including Alzheimer's, Parkinson's, and amytrophic lateral sclerosis (ALS), affect millions of people worldwide and represent an increasing burden in terms of healthcare economics and societal impact. The investigation and characterization of the abundance, specific spatial distribution and co‐localization of neurodegenerative and neuroinflammatory targets within the human brain are critical for the advancement of our understanding of progressive degenerative disease. Method: NanoString's GeoMx Digital Spatial Profiler (DSP) platform allows for simultaneous analysis of >70 proteins from discrete regions of interest (ROI) in FFPE tissue sections, providing morphological context to high plex molecular analysis. The assay relies upon antibody probes coupled to photocleavable oligonucleotide tags. After hybridization of probes to slide‐mounted formalin fixed paraffin‐embedded (FFPE) tissue sections, the oligonucleotide tags are released from discrete regions of the tissue via UV exposure. The size and shape of the UV exposure pattern is adjustable allowing for precise investigation into rare or specific cell populations, disease microenvironments, or neural sub‐regions. Released tags are quantitated on the standard nCounter® platform, and counts are mapped back to tissue location, yielding a spatially‐resolved digital profile of analyte abundance. Results: In this study, we validate the GeoMx Human Neural Cell Profiling Core panel (∼20‐plex, RUO) and five add‐on Modules (∼10‐plex each, RUO) covering Alzheimer's Pathology, Parkinson's Pathology, Autophagy, and Glial Cell Subtyping on GeoMx DSP platform. In addition, diseased human brain tissue was mapped with fluorescent morphology markers highlighting amyloid beta plaques, microglia, and astrocytes to select ROIs for high plex profiling using the validated antibody set. In comparable studies, mouse neurodegenerative disease models were evaluated with the GeoMx Mouse Neural Cell Profiling Core panel and Alzheimer's and Parkinson's Pathology Modules in both FFPE and fresh frozen samples. Conclusion: Specific cell population sampling was demonstrated by masking for multiple or individual microglia, neurons, and astrocytes. Concentric masks around plaques (Contour Profiling) allowed for spatially distinct sampling of the amyloid beta plaque microenvironments. Ongoing efforts will expand the neuroscience‐specific human and mouse antibody catalogues validated for the GeoMx DSP platform.